Origin and Fates of TERT Gene Copies in Polyploid Plants - Fajkus, Petr; Peška, Vratislav; Fajkus, Jiří; Sýkorová, Eva (International journal of molecular sciences, 2021)
The gene coding for the telomerase reverse transcriptase (TERT) is essential for the maintenance of telomeres. Previously we described the presence of three TERT paralogs in the allotetraploid plant Nicotiana tabacum, while a single TERT copy was identified in the paleopolyploid model plant Arabidopsis thaliana. Here we examine the presence, origin and functional status of TERT variants in allotetraploid Nicotiana species of diverse evolutionary ages and their parental genome donors, as well as in other diploid and polyploid plant species. A combination of experimental and in silico bottom-up analyses of TERT gene copies in Nicotiana polyploids revealed various patterns of retention or loss of parental TERT variants and divergence in their functions. RT-qPCR results confirmed the expression of all the identified TERT variants. In representative plant and green algal genomes, our synteny analyses show that their TERT genes were located in a conserved locus that became advantageous after the divergence of eudicots, and the gene was later translocated in several plant groups. In various diploid and polyploid species, translocation of TERT became fixed in target loci that show ancient synapomorphy.
Keywords: proteiny huseníčku; Gene Dosage; genová dávka; polyploidy; Arabidopsis Proteins; Polyploidy; synteny; gene evolution; Nicotiana; telomerasa; Telomerase; telomerase; tabák; Arabidopsis; polyploidie